Clinical and microbiological characteristics of community-acquired pneumonia associated with Streptococcus pneumoniae in adult patients in Mexico - Echániz Aviles, Gabriela; Garza González, Elvira; Román Mancha, Alma Lucía; Morfín Otero, Rayo; Rodríguez Noriega, Eduardo; Ayala Gaytán, Juan Jacobo; Guajardo Lara, Claudia Elena; Soto Nogueron, Araceli; Carnalla Barajas, Maria Noemí; Camacho Ortiz, Adrián (2019)
Time and risk management have always been major concerns in a continously growing number of processes and methodologies used to develop all kinds of useful products and services. Software like any other industry not only needs the most appropriate development methodology but also an efficient project management strategy that is capable of estimating and managing development times and any potential risks as best as possible in order to deliver high quality software products and services on time. Hence, the success or failure of software development projects depends on the efficiency by which several key factors such as cost, time, and risks are managed and how other software development factors influenced them. This paper presents an exploratory factor analysis to study the effects produced primarily on time planning caused by common factors observed in outsourced software development projects such as communication, teamwork, personnel training, among others. In our work, we also build a structural model in which we analyze the relationships between sets of dependent and independent variables derived from the responses of a survey applied to 32 Mexican organizations that subcontracted their software development projects to outsourcing providers. The results are presented and the reliability of our model was validated using the SmartPLS software